Review of the genus Mimophytum Greenm. (Boraginaceae) - Pérez-Calix, Emmanuel; Patiño-Siciliano, Alfredo (Instituto de Ecología, A.C., 2009)
A morphological description of the genus Mimophytum Greenm. (Boraginaceae) is provided, as well as a dichotomous key to the species and ecological and distributional information. The genus is endemic to the Sierra Madre Oriental of Mexico. Morphological descriptions for the two species are provided. One of them, M. benitomartinezii, is proposed as new to science. It differs from M. omphalodoides in that the stems are rhizomatous-stoloniferous, the upper leaf surfaces are glabrous, the leaf blades possess 3 basal nerves, the inflorescence is an ebracteate, scorpioid cyme, the pedicels are shorter, and the fruits have glochids forming a ring around the edges.